State and Problems of Using Professional Learning Community through Lesson Study in Kindergarten under The Bureau of Education Pattaya - Kaenprayoon, Kawinna; จารุชัยนิวัฒน์, ปนัฐษรณ์ (An Online Journal of Education, 2023)
The purpose of this research was to study the conditions and issues related to the use of professional learning communities through lesson study at the kindergarten level under the Bureau of Education in Pattaya, in three aspects: preparation, implementation, and reflection. The research population consisted of 80 kindergarten teachers. The research instruments used were questionnaires, and data were analyzed using frequency analysis, percentage, and content analysis. The research findings showed that the problems with professional learning communities through lesson study at the kindergarten level under the Bureau of Education in Pattaya can be summarized as follows: 1) Preparation:, Teachers encountered problems setting goals for collaborative learning management development (37 people), problems related to the exchange of perspectives and experiences, and assessment of learning management for kindergarten-aged children (23 people). 2) Implementation:, Teachers encountered problems with the implementation of plans in learning management (33 people), which is a problem with organizing activities for children to apply knowledge or apply knowledge to give back to society (17 people) 3) Reflection:, Teachers continuously encountered problems in the development of collaborative learning management (27 people), which is a problem in improving the management of learning to be effective (14 people).